2022
DOI: 10.1101/2022.09.01.506173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZEB2 regulates the development of CD11c+ atypical B cells

Abstract: CD11c+ atypical B cells (ABC) are an alternative memory B cell lineage identified both in normal immune responses as well as pathogenic responses in autoimmunity. While it is clear that ABCs have a distinct transcriptional program, the factors that direct this program have not been identified. Here, we generated a human tonsil single-cell RNA-seq dataset and identified candidate transcription factors associated with the ABC population. We selected 8 of these transcription factors for further analysis based on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The up or down regulation of various genes in these clusters as compared to resting switched memory B cells in cluster 3 was consistent with previous reports ( Figure 3A ). Two manuscripts recently posted on bioRxiv showed that the transcription factor ZEB2 acts as an important regulator for the development of atypical B cells ( 24, 25 ). ZEB2 was also expressed significantly higher in clusters 1, 4, and 5 as compared to cluster 3 ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…The up or down regulation of various genes in these clusters as compared to resting switched memory B cells in cluster 3 was consistent with previous reports ( Figure 3A ). Two manuscripts recently posted on bioRxiv showed that the transcription factor ZEB2 acts as an important regulator for the development of atypical B cells ( 24, 25 ). ZEB2 was also expressed significantly higher in clusters 1, 4, and 5 as compared to cluster 3 ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…5D,E ), and Regnase-1 deficiency at earlier stages of B cell development in mice produces severe autoimmune immunopathology and early mortality, accompanied by ABC expansion ( 88 ). TBX21 (encoding TBET ), ZEB2 and EGR3 are important and potential master regulators of ABC development and/or function in mice and humans ( 23, 25, 26, 49 ), and each were Up DEGs in either ‘memory’ Cluster 5 ( TBX21 , ZEB2 ) or activated Cluster 9 ( EGR3 ), Fig. 5C,E .…”
Section: Resultsmentioning
confidence: 99%
“…TBX21 (encoding TBET), ZEB2 and EGR3 are important and potential master regulators of ABC development and/or function in mice and humans (23,25,26,49), and each were Up DEGs in either 'memory' Cluster 5 (TBX21, ZEB2) or activated Cluster 9 (EGR3), Fig. 5C,E.…”
Section: Genes Critical For B Cell Fate and Function Are Differential...mentioning
confidence: 99%
See 2 more Smart Citations